Penerapan Kurikulum Merdeka di Sekolah: Studi Perbandingan antara Sekolah Negeri dan Swasta - Hanifah Maulidia; Nada Gustiani; Gusmaneli (GLOBAL SCIENTS PUBLISHER, 2024)
The Independent Curriculum is an educational program introduced in 2022, which aims to provide autonomy to schools in preparing a curriculum that suits students' needs. This approach emphasizes student-oriented learning, with a focus on developing individual potential and life skills. In its implementation, the Independent Curriculum faces a number of challenges, such as the large number of students, limited resources, and teachers' difficulties in adapting to new methods. However, some schools have succeeded in implementing this curriculum well, showing that the right support can improve the quality of education. Private schools, with more flexibility, have the opportunity to design innovative learning programs, although they still face the same challenges. Parent and community involvement is very important to support the successful implementation of this curriculum.